EXPERT SYSTEM KERONTOKAN RAMBUT PADA BAYI MENGGUNAKAN METODA BACKWARD CHAINING - Yogi Wiyandra; Firna Yenila; Wifra Safitri (Jurnal Teknologi Informasi dan Pendidikan, 2017)
Expert System is designed to know the cause of hair loss in infants. It is expected that the system designed to help parents, especially mothers in understanding the condition of babies who have hair loss. This built system is a system that moves the science of an expert into the application with Backward Chaining method that has a goal to provide understanding to parents in overcoming hair loss baby. Keywords: Expert System, Backward Chaining, Hair Loss